Woodfuel Production and its Implication in Driving Deforestation in the Drylands of Ethiopia - Girma, Gonche A.; Shimeles, Abebaw (Graduate School, Universitas Brawijaya, 2025)
The derived motives of people in the drylands while performing woodfuel production are primarily to support their livelihoods and source of energy in dryland areas. Besides to its significant roles, it has also undoubted multiple negative effects. However, there is little information documented that would help policy and development interventionists to mitigate those effects. Therefore, this study assesses the deforestation and environmental implications of woodfuel production activity. The result shows that dependence on woodfuel (charcoal and firewood) income increases markedly from farming to pastoral groups, becoming the dominant income source for both agro-pastoral and pastoral households. This pattern underscores the critical role of woodfuel in rural livelihoods, especially where agricultural productivity is low. Poverty, unemployment, and the requirement for energy are main reasons of woodfuel dependency. However, woodfuel producers do not create their own gacor slot plantations for the extraction of woodfuel. They merely rely on the forest resources to meet their requirements. Deforestation, soil loss, and loss of biodiversity gacor slot were some of the environmental problems that arose from woodfuel production. The study result recommended a policy direction to support the adoption of sustainable woodfuel production practices such as plantations, assisting natural regeneration based on the local context of dryland areas